Indigenous education: A nomatsigenga people own education - Shoente Chumpate, Jaime (2017)
A proposal of own indigenous education of the Nomatsigenga people is presented in this article. It is based on an educational experience in the classroom, in four Nomatsigenga schools of a unique-teacher and multi-teacher type where Intercultural Bilingual Education (IBE) is applied. We propose guaranteeing the active participation of the Nomatsigenga wise people in the entire school process. It means that these wisepeople will express their points of view and will decide about the sociocultural diagnosis, the elaboration of the school's curricular design and also the didactic process in the classroom, from peer to peer with the IBE teachers appointed by the State.